2015
DOI: 10.1128/aem.01353-15
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the In Vitro Activity of the Cyclosporine-Specific P450 Hydroxylase from Sebekia benihana and Development of a Heterologous Whole-Cell Biotransformation System

Abstract: cThe cytochrome P450 enzyme CYP-sb21 from Sebekia benihana is capable of catalyzing the site-specific hydroxylation of the immunosuppressant cyclosporine (CsA), leading to the single product ␥-hydroxy-N-methyl-L-Leu4-CsA (CsA-4-OH). Unlike authentic CsA, this hydroxylated CsA shows significantly reduced immunosuppressive activity while it retains a side effect of CsA, the hair growth stimulation effect. Although CYP-sb21 was previously identified to be responsible for CsA-specific hydroxylation in vivo, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…The Hill equation can be used to indicate cooperative kinetics. Indeed, several studies have found that some P450s are able to fit into its active site with large molecules such as cyclosporine [ 60 ] or two substrates at once [ 57 ]. The two substrates can be the same or different molecules allowing the homotropic or heterotropic cooperative kinetics, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Hill equation can be used to indicate cooperative kinetics. Indeed, several studies have found that some P450s are able to fit into its active site with large molecules such as cyclosporine [ 60 ] or two substrates at once [ 57 ]. The two substrates can be the same or different molecules allowing the homotropic or heterotropic cooperative kinetics, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the protein pair SelFdx1499 (Fe 2 S 2 )/SelFdR0978 (plastidic-type FdR) from the cyanobacterial strain Synechococcus elongatus PCC 7942 has been shown to be an optimal combination for supporting in vitro reactions of prokaryotic P450s, including MycG, PikC, P450sca-2 and others (76). Besides the above-mentioned P450 reaction matrix network, the protein pair SelFdx1499/SelFdR0978 has also been shown to be optimal for the site-selective hydroxylation of CsA by CYP-sb21 and CYP-pa1 (45,47), the uncommon ester-to-ether transformation catalyzed by Rif16 in rifamycin biosynthesis (77), the tandem ether installation and hydroxylation by AmbV involved in neoabyssomicin/abyssomicin biosynthesis (78), and the biosynthesis of phenylserine (␤-OH-Phe) unit in atratumycin by Atr27 (79).…”
Section: Redox Partner Engineeringmentioning
confidence: 99%
“…Given the attractive advantages of conventional water-miscible organic solvents, including their simple management, high solubility for various organic substances, and capacities to improve the enantio-selectivity and activity of biocatalysts [11,12], organic solvents have been used as "cosolvents" and "permeability enhancers" to stimulate substrate transfer across cells [7,10], but the choice and amount of added organic solvent are highly empirical and generally undesirable for large-scale applications [13]. In most single-enzyme whole-cell catalytic processes, dimethyl sulfoxide (DMSO) and methanol (MeOH) are commonly used as solubility enhancers to promote the biosynthesis of glycosides and hydrophobic compounds [14,15]. The use of a recombinant single enzyme overexpressed in Escherichia coli is employed as a whole-cell biocatalyst treated with 60% acetone (v/v) [16] or 10% ethanol (EtOH) [11] to enhance the permeabilization of cell membranes and, further, to promote high yields of L-phenylalanine and L-menthol.…”
Section: Introductionmentioning
confidence: 99%